Achieving Sustainable Workplace Wellbeing - Daniels, Kevin; Tregaskis, Olga.; Nayani, Rachel; Watson, David (Cham : Springer International Publishing : Imprint: Springer, 2022)
In this groundbreaking interdisciplinary work, the authors focus on organizational analysis to understand workplace wellbeing, deviating from previous research that mostly looks at the individual worker or intervention. In addressing the question of why workplace health and wellbeing practices initiatives fall short of delivering sustained improvements in worker wellbeing, this book moves beyond localized explanations of the failure of specific interventions. Instead, it creates theoretical frameworks that explain how wellbeing at work can be improved and sustained. The authors use evidence from systematic and comprehensive surveys of the literature as well as new empirical research, and present an explanatory framework of the processes through which organizations change to implement and accommodate workplace health and wellbeing practices. Learning, adaptation and continuation explain successful implementation of workplace health and wellbeing practices, while Gestalting, fracturing and grafting explain how organizations resolve or negotiate conflict between health and wellbeing practices and existing organizational procedures, systems and practices. In addition, the authors reflect on the implications for research of reframing the unit of analysis as the organization and how studies on workplace wellbeing practices can provide a conceptual platform for thinking about the way organizations can create social value in a broader sense. This book, authored by experts in their field, is a great resource for academics and professionals of organizational studies and of worker wellbeing across the social sciences, behavioural sciences, business and management courses, wellbeing research, and labour studies.
Part 1: Conceptual background -- Introduction -- Conceptual models of implementation -- Part 2. Research on implementation -- Context - discrete - tangible changes, intended and emergent mechanisms -- Context - competing logics -- Context - delivery - governance, signals and evaluation -- Studies of implementation: How organisations make things work - learning, adaptation and continuation -- Putting the workplace back into workplace wellbeing -- Part 3. Looking forward -- Intentions, emergence and authenticity -- Conclusions and extensions.
Keywords: Employee health promotion; Organizational sociology; Occupations-Sociological aspects; Personnel management; Occupational health services; Psychology, Industrial; Employee Health and Wellbeing; Sociology of Organizations and Occupations; Human Resource Management; Occupational Health; Work and Organizational Psychology